The effects of elevated temperature and fiber reinforcement on fly ash based geopolymer concrete / Navid Ranjbar - Navid, Ranjbar (2015)
Geopolymers are formed through the hydrothermal synthesis of aluminosilicate sources in the presence of alkali activators such as sodium hydroxide (NaOH) or sodium silicate (Na2SiO3) which cure and harden at near ambient temperatures. Due to ceramic-like characteristics, geopolymers show high quasi-brittle behaviour and are much less resistant to tensile load than compressive; however, it shows higher degree of resistance to elevated temperatures. This research investigates the fundamental material properties and structural response of geopolymer concrete developed using the two types of locally available materials in Malaysia to produce a new constructional binder as a replacement of the conventional Portland cement based products. This research is composed of four major aspects of the research findings that are reported in the form of six articles. In the first section, the fundamental differences between low and high Si/Al ratio geopolymers developed using fly ash (FA) and Palm Oil fuel ash (POFA) precursors is discussed. In the second part, the response of the proposed geopolymers is determined under elevated temperatures of 300C, 500C, 800C and 1000C to characterize the mechanical properties enhancement by heat treatment and their thermal resistance. Overcoming the brittleness of the FA based geopolymer by incorporation of fibers with different scales and material properties is the next phase of the research. And finally, structural application of the geopolymer material using novel multi-layer composite beams was done and verified by elastic theories and ACI 318-14. Based on the results obtained, it is observed that the particle shapes and surface area of POFA and FA as well as chemical composition affects the density and compressive strength of the mortars. The increment in the percentages of POFA increased the SiO2/Al2O3 ratio and that resulted in reduction of the early compressive strength of the geopolymer and delayed the geopolymerization process. Moreover, replacement of the v POFA in FA based geopolymer mortar expedited the start of micro-pore formation when the corresponding geopolymer specimens were exposed to high temperatures and shifted the ultimate strength peak from 300 °C to 500 °C. The addition of 1% graphene nanoplatelets (GNP) enhanced the compressive and flexural strength of the fly ash based geopolymer by 1.44 and 2.16 times, respectively. The point of interest is that introduction of GNP filler even at low filler weight fractions increased the toughness, stress and strain at the first crack and rigidity. Moreover, the wettability decreased with the increase of GNP content. It is observed that the degree of shrinkage of the polypropylene fiber reinforced geopolymer composite is minimized by addition of 3% of fiber into the geopolymer matrix; meanwhile, the presence of polypropylene fiber in fly ash based geopolymer matrix did not increase the flexural and compressive strength but did lead to enhanced post-peak load carrying capacity and energy absorption. On the other hand, micro steel fiber has the potential to minimize dry shrinkage of fly ash based geopolymer matrix in addition to significant increase in flexural strength and flexural toughness of the composites; it also enabled transformation of the brittle behaviour to ductile mode without an adverse effect on ultimate compressive strength. However, like other fibers, incorporation of micro steel fiber led to reduction in flow and workability of the composite in fresh state. Based on experimental results obtained from beam specimen tests, it was observed that the geopolymer beam showed about double deflection relative to the ordinary Portland cement based beams; however the ultimate load capacity was quite similar. Results showed that by increasing the geopolymer layer thickness in composite beams, ductility and energy absorption of the beams were increased and mode of damage was shifted from shear to flexural. Moreover, formation of horizontal shear cracks in composite beams at the interface of the layers limited the crack propagation to the geopolymers section causing a larger damage zone and corresponding toughness enhancement. The experimental results were also compared to elastic theory and ACI 318-14.